C-reactive protein/albumin ratio as a predictor of 28 day mortality in patients with sepsis - T., Hamsa B.; V., Srinivasa S.; A., Raveesha (International Journal of Research in Medical Sciences, 2020)
Background: Sepsis is defined as life-threatening organ dysfunction caused by a dysregulated host response to infection. Sepsis remains a major cause of morbidity and mortality worldwide. Important biomarkers that can be used as prognostic markers in sepsis are C Reactive Protein (CRP) and serum Albumin levels. CRP levels markedly elevate in response to infection whereas albumin levels decrease in response to acute phase infection. We want to ascertain the value of CRP/albumin ratio as an independent predictor of 28-day mortality in sepsis patients. Methods: A prospective study was conducted including 150 patients satisfying the criteria for sepsis according to SOFA score of more than 2. Initial CRP/Albumin ratio was assessed to determine its significance in assessing the 28-day mortality, primary end point of our study. Secondary end points assessed were length of ICU stay, need for inotropic support, need for ventilator support and renal replacement therapy. Results: In the analysis of CRP/Albumin ratio as a predictor of 28-day mortality, patients were followed up from day of admission till 28 days to assess primary outcome. Among study subjects survivors were 92 in whom mean CRP/ALB ratio was 0.1197 and non survivors were 58 patients with mean CRP/ALB ratio was 0.0426. p-value <0.001, there was statistically significant difference found between survivor and Non-Survivor with respect to CRP/Albumin ratio. In assessing secondary outcome statistically significant association was found for need for ventilator and inotropic support, whereas it was insignificant in assessing need for dialysis and length of ICU stay. Conclusions: CRP/albumin ratio, which indicates the extent of residual inflammation, could be used as a prognostic marker in predicting mortality in patients with sepsis and septic shock.